The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3329/ujzru.v31i0.15435
|View full text |Cite
|
Sign up to set email alerts
|

Constraints and prospects of carp production in Rajshahi and Natore districts, Bangladesh

Abstract: : This study was conducted in Rajshahi and Natore districts of northern area of Bangladesh for a period of three years (2007 to 2009). One hundred carp ponds were selected randomly and fish farmers were interviewed to reveal the existing constraints and prospects. Ten percent farmers reported multiple ownership as a problem and 16% farmers stated that lease value of pond is too high which reducing their profit level. Lack of quality fish seeds was reported by 33% farmers which results in low growth and high mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 5 publications
(8 reference statements)
2
15
0
Order By: Relevance
“…Likewise, the average production was 2,900 kg/ha/yr in Shahrasti, Chandpur (Pravakar et al, 2013), 2,925 kg/ha/yr in Gazipur district (Rahman, 2003) and also the same carp production was found in Bhaluka, Mymensingh (Kamruzzaman, 2011) and 2,940 kg/ha/yr in Moulvibazar (FRSS, 2015). On the other hand, mean (±SD) fish production was found 3,598.72±785.83 kg/ha/yr in carp polyculture of Rajshahi and Natore districts (Mohsin et al, 2012) and 3,743 kg/ha/yr in Mymensingh (Biswas, 2003). The annual production varies because of differences in pond size, depth, categories, feed, seed, other inputs and management practices.…”
Section: Fish Production Cost and Profitmentioning
confidence: 99%
“…Likewise, the average production was 2,900 kg/ha/yr in Shahrasti, Chandpur (Pravakar et al, 2013), 2,925 kg/ha/yr in Gazipur district (Rahman, 2003) and also the same carp production was found in Bhaluka, Mymensingh (Kamruzzaman, 2011) and 2,940 kg/ha/yr in Moulvibazar (FRSS, 2015). On the other hand, mean (±SD) fish production was found 3,598.72±785.83 kg/ha/yr in carp polyculture of Rajshahi and Natore districts (Mohsin et al, 2012) and 3,743 kg/ha/yr in Mymensingh (Biswas, 2003). The annual production varies because of differences in pond size, depth, categories, feed, seed, other inputs and management practices.…”
Section: Fish Production Cost and Profitmentioning
confidence: 99%
“…The minimum value was recorded in T 2 whereas the maximum value was recorded in T 3 . DoF [8] reported that in a water body the suitable range of DO for fish culture would be 5-8 mg/1. Asadujjaman et al [22] observed that dissolved oxygen ranged between (5.45 to 7.78 mg/1) during their experiment in BAU campus, Mymensingh.…”
Section: Water Quality Parametersmentioning
confidence: 99%
“…In Bangladesh, culture-based fisheries and smallscale aquaculture are often constrained by the lack of suitably sized seed stock. Although there is a large quantity of fry of cultured species in particular carp species produced in Bangladesh, fingerling production has lagged behind due to economic and land constraints [8]. Promoting cage culture could meet the demand of land for fish farming.…”
Section: Introductionmentioning
confidence: 99%
“…Carp contributes 52.06% of the total pond production in Bangladesh (FRSS, 2020). Aquaculture, especially carp culture, is essential for supplying nutrition, income and employment in Bangladesh (Mohsin et al, 2012). It has the advantages of easy access and developed market demands over the other aquaculture practices.…”
Section: Introductionmentioning
confidence: 99%